Оцінювання сучасних змін термічного режиму України - Балабух, В.О.; Малицька, Л.В. (Геоінформатика, 2017)
Досліджено характерні риси термічного режиму в Україні у сучасний кліматичний період (1981—2010) та його особливості відносно базового кліматичного періоду (1961—1990). Уточнено тенденції змін кліматичних середніх і показників екстремальності термічного режиму на межі ХХ та ХХІ ст. Для кожної адміністративної області та країни в цілому оцінено статистичну значущість, імовірність і частку невизначеності виявлених змін. Установлено суттєві зміни кліматичних показників термічного режиму, які привели до зміни їх середніх багаторічних значень у сучасний кліматичний період і, відповідно, до зміни кліматичної норми відносно базового кліматичного періоду. Виявлено залежність між величиною аномалії середньої за рік температури повітря і аномаліями показників термічного режиму. Исследуются характерные черты термического режима в Украине в современный климатический период (1981— 2010) и его особенности относительно базового климатического периода (1961—1990). Уточнены тенденции изменений климатических средних и показателей экстремальности термического режима на рубеже XX—XXI вв. Для каждой административной области и страны в целом оценена статистическая значимость, вероятность и доля неопределенности выявленных изменений. Выявлены существенные изменения климатических показателей термического режима, которые привели к изменению их средних многолетних значений в современный климатический период и, соответственно, к изменению климатической нормы относительно базового климатического периода. Установлена зависимость между величиной аномалии средней за год температуры воздуха и аномалиями показателей термического режима. Purpose The aim of the study is to assess the state and the current changes of meteorological parameters of the thermal regime in Ukraine through the current climatic period (1981—2010).
Design/ methodology/ approach The research of features and changes of the thermal regime, and the characteristics of its extreme was conducted for the period of 1981—2010 using the daily data on the average, minimum and maximum surface temperature from the 187 meteorological stations across Ukraine. Based on the daily observation data, we calculated the characteristics of the thermal regime: average, minimum and maximum per year and season air tem¬perature, the number of warm, summer and hot days, tropical nights, frost days and days with frost below -10 °C and -20 °C, the number of days, favourable for vegetation and days requiring heating, the maximum duration of the hot period and period of extreme cold. For each meteorological parameter the current climatic norm (1981—2010), rate and direction of changes, its significance and reliability were determined for all regions of Ukraine and the country as a whole. The reliability of the change was evaluated according to Student’s t-test.
Findings The article considers the characteristics of thermal regime in Ukraine in the current climatic period (1981— 2010) and its features relative to the basic climatic period (1961—1990). We have also specified the trends of change in long-term values of average and extreme characteristics of the thermal regime at the turn of the 20th and 21st centuries. The conducted analyses revealed that in 1981—2010 the climatic norms for the main parameters of the thermal regime rose against the values for the basic climatic period (1961—1990) due to significant increase in the air temperature. It was discovered that the air temperature in Ukraine increased throughout the year at a much faster pace than globally. Such changes in winter season led to a decrease in the cold period duration, the number of cool days and the number of days requiring heating. In the warm period, there is a tendency to increase the duration of the warm and summer periods and the period of vegetation, as well as the number of hot days and the duration of the hot period. These changes have regional peculiarities and increase from south to north. There is a relationship between the anomalies of the average annual air temperature and the anomalies of the climatic parameters of the thermal regime. We have found that an increase in the average annual temperature by 1 °С leads to an increase in the duration of warm and vegetative periods in Ukraine for 6—7 days per 10 years and the number of summer days for 4 days per 10 years. The growth of the average summer temperature by 1 °C causes an increase in the number of hot days for 8 days per 10 years. These dependencies have also regional features.
Practical value/ implications The identified regional features of the thermal regime in Ukraine and their changes must be taken into account in the production activities of the climate-dependent industries of the country’s economy, above all in those regions where their probability is the greatest. The results can be used for assessing the socio-ecological and socio-economic impacts of climate change and climatic projections made for different greenhouse gas emission scenarios and community development.